Electrode-nanoparticle collisions: The measurement of the sticking coefficient of silver nanoparticles on a glassy carbon electrode - Zhou, Y; Rees, N; Compton, R (2011)
In this communication, we combine anodic particle coulometry (APC) with anodic stripping voltammetry, to find the proportion of NP impacts that result in adsorbed NPs, using AgNPs in collision with glassy carbon electrode. Sticking coefficients are reported for AgNP radii of 14, 29, and 45 nm, measured at electrode biases ranging from OCV to -0.2 to -1.2 V (vs. Ag/AgCl). No significant systematic trends were found in either case. We suggest that this methodology may be widely applicable to measuring the sticking coefficient of any oxidisable metal nanoparticle on an electrode surface in solution. © 2011 Elsevier B.V. All rights reserved.